Janeway's Immunobiology. - Murphy, Kenneth Travers, Paul Walport, Mark (Garland Science, 2008)
"Janeway's Immunobiology, Seventh Edition is an introductory text for use in immunology courses for undergraduates, graduate students and medical students. The Seventh Edition has been updated throughout, and includes new information on topics such as NK cells, Toll-like receptors, AID, viral evasins, mucosal immunity, and celiac disease, to name a few. Each copy of the book includes a revised CD-ROM, Immunobiology